Higher education regionalism in Asia: what implications for Europe?. Issue 1 (2nd January 2019) - Cabanda, Exequiel; Tan, Ee Siong; Chou, Meng-Hsuan
ABSTRACT: Studies of regionalism – intra and comparative regionalism – have often used the European experience to explain the emergence and evolution of regionalisms in other parts of the world. This tendency in approaching the European experience as explanatory has permeated sector-specific developments. In this article, we consider the developments in higher education to examine the purported influence that Europe's Bologna Process has had on other regional initiatives. Taking the case of the Asian Universities Alliance (AUA), we delineate the narratives from the actors involved in this initiative to show how they initially perceived and conceptualized higher education cooperation in the Asia region. Applying higher education regionalism framework, we show how AUA actors designed higher education regionalism in Asia independent from Europe's influence. We conclude with the potential implications that AUA's emergence has for Europe, taking into consideration the growing influence of China in developing higher education regionalisms in Asia.